USING ENGLISH SONGS IN IMPROVING LISTENING SKILL - Putri, Cindiyana Muryani; Bunau, Eusabinus; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed at improving students’ listening skill in Class Eleven Multimedia of Vocational High School Mandiri Pontianak in Academic Year 2017/2018. This research used English songs as technique in teaching listening. This research was done by giving students Fill in the Blank song lyrics. The method of this research was classroom action research, which consisted of 2 cycles. The subject of this research was students of Class Eleven Multimedia of SMK Mandiri Pontianak in academic year 2017/2018. The research was conducted to solve the problem encountered by the students in listening. Most of the students were not able to listen well because they lacked of vocabulary. The technique of data collecting for this research was observation and test. The tools of data collecting were listening test, observation checklist, and field note. The result of this research showed that English songs improved students’ listening skill by Filling in the blank song lyrics. The students’ individual score in listening also improved in teaching learning process. From this result, it can be concluded that students’ listening taught by English songs had improved. In another word, this media can help students in listening. Keywords: English Songs, Listening, Classroom Action Research.